REKONSTRUKSI KARAKTER PANCASILA TERHADAP PESERTA DIDIK - Aris Wijaya; Anisa Rahman; Sri Yunita; Yacobus Ndona (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Facing the developments of the times, starting from digital technology to culture, where many national characters do not adhere to the values and morals of Pancasila. Pancasila education plays a crucial role in reconstructing characters, especially among students. Characters aligned with Pancasila will shape a nation of quality individuals who care deeply for their country and possess a high level of nationalism. The method used in this research is descriptive qualitative, aimed at examining the problems, challenges, solutions, and obtaining information regarding the reconstruction of Pancasila character education for students. The results of this research indicate that the younger generation, as the successors of national leadership, must be able to become good citizens. This can be achieved by instilling Pancasila values from an early age. Pancasila values act as a bond and driving force in efforts to defend and fight for independence, making them in line with the personality and desires of the Indonesian nation. There are three approaches to reconstructing Pancasila character: Role Modeling, Conditioning, and Teaching.